Contract and Tort Law Aspects of the Performance of Duties of Notaries Public - Principles of the law pertaining to notaries public, notarial deed and liability of notaries public according to the Serbian law - - Szalma, József (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
In this paper the author analyzes the effective Serbian rules of law on notaries public, in comparative perspective. The principles of law pertaining to notaries, the notarial deed and the legal nature of the notaries’ liability for damages are discussed. Special emphasis is given to the principles of public confidence, legality, professionalism, formalism and independence, from which the notaries’ liability for damages caused to clients and third parties derives. Although the notaries public are independent, hence they are not subordinate to any judicial or administrative organ, their liability for damages is analogous to the liability of administrative organs, whereby the condition of filing a legal remedy is construed in a fairly broad sense, that is any remark of the client disclosed to the notary is considered as filing a legal remedy. The author’s standpoint is that the legal nature of notary’s liability is either contractual or delictual, depending on whether the notary infringed a clause of the mandate of the client, which serves as the legal ground of his/her actions, or mandatory rules, that is the statutory requirement of acting in good faith. Besides general rules on the requirements of form of juridical acts (essential form, facultative form), the subject of analysis are also the rules on exclusive and alternative (competing) forms of notarial deeds. The effective Serbian law on notaries public envisages the form of notarial deeds and private instruments predominantly as alternative forms, that is a specific kind of deed has the same legal effect, regardless whether it is drafted by a notary or concluded in court.
Keywords: notary’s liability for damages; notarial deed; principles of the contract and tort law aspects of performing of the duties of notaries public